Capital structure before and after merger and acquisition: banking industry in Malaysia - Ong, Tze San; Ng, Phing Phing (QS Publications, 2013)
During the Asian financial crisis in year 1997, countries under International Monetary Fund (IMF) programmes are required to close down the small and weakest banking institutions. However, Malaysia government denied and initiated a robust bank merger programme to restructure all the fifty four financial institutions into ten anchor banks in year 1999. By the end of 2011, there were only eight anchor banks in Malaysia. Today, Malaysian Government still encourages companies in Malaysia to participate in the merger and acquisition activities. Previously, many studies were done according this issue by using Data Envelopment Analysis (DEA). However, the impact of merger and acquisition of Malaysian Bank is still vague. Hence, this paper attempts to examine the impact of merger and acquisition of Malaysian bank by using capital structure. This paper focuses on seven pairs of anchor banks which merged and acquired other minor banks in Malaysia from year 1999 until 2006. This paper uses descriptive statistic to compare the capital ratios and profitability ratios of 5 years before and after merger and acquisition to identify the impact. Besides, regression analysis used to determine the relationship of independents variables and dependent variables. The overall result of this study proved that merger and acquisition in Malaysian anchor banks do not significant increment the capital structure of bank. However, the result of ROA and ROE indicate performance of banks will improve after merger and acquisition. On the other hand, EPS indicate the shareholder’s value will slightly diminished after the merger and acquisition. Moreover, the result in more attentive view (changes of capital structure and performance of each pair of bank) indicates not all bidders and targets will had better performance after the consolidation. This proved that merger and acquisition do not solely brought benefit to the bank and country’s economy. The impact of merger and acquisition will affect by the bidder and target condition, economic condition and other external factors.